Examining the Spatial and Temporal Relationships among Aerosol Optical Depth, Soil Moisture, and Wind Speed from 2000 to 2024,(Case Study: Western Iran) - Sosan Salajegheh; Hamed Eskandari Damaneh; Hadi Eskandari Damaneh (Desert)
Dust storms create considerable environmental issues in many arid and semi-arid regions such as Iran. Hence, recognizing dust storm patterns is essential for lessening their adverse impacts. This study has utilized Aerosol Optical Depth (AOD) data from a MODIS satellite sensor, along with SW indices and Wind Speed (WS) data sourced from ERA5 reanalysis data. Subsequently, the trends of these indices were examined using the Mann-Kendall test and trend slopes from 2000 to 2024. Then, the correlation between these data was evaluated in research study period. The trend analysis results based on the Z Mann-Kendall test and Sen's slope estimator showed that the dust index AOD generally had an increasing trend in western Iran during this period. Specifically, an area of 65,143.8 km2 exhibited an increasing trend, with 31,243.8 km2 of this area being statistically significant. Most of this area is located in the south and southwest of the study region, which has the lowest soil water and the highest wind speeds. The correlation analysis between the dust index AOD and the two indices of soil water and wind speed showed a negative correlation between AOD and SW index in 78,543.8 km2, of which 38,643.8 km2 were statistically significant. The correlation between the dust index AOD and WS also showed a positive correlation in 61,343.8 km2 of the study area, with 8,343.8 km2 of this being statistically significant. In general, we can conclude that biophysical factors, like soil moisture, and climatic factors, such as wind speed, significantly affect dust levels. Continuous monitoring of these parameters and evaluating their impact on sensitive and fragile ecosystems can help enhance resilience to dust in these regions.